Re-uniting the Caribbean 'a new beginning' - John, Kenneth (National Advisory Committee on Political Union in the EastCaribbean [Kingston]VC, 1990)
Presents 15 articles published in 'the Vincentian' newspaper focusing on East Caribbean unity.